The Mediterranean bioconstructor Lithophyllum stictiforme shows adaptability to future warming - Pinna, Federico; Caragnano, Annalisa; Piazzi, Luigi; Ragazzola, Federica; Stipcich, Patrizia; Rindi, Fabio; Ceccherelli, Giulia (Frontiers in Marine Science, 2022)
Understanding how coralline algae may acclimatize to ocean warming is important to understand their survival over the coming century. Taking advantage of natural differences in temperature conditions between coastal areas in Sardinia (Italy) and between depths, the responses in terms of biological traits to warming of the crustose coralline alga Lithophyllum stictiforme, a key bioconstructor of coralligenous reefs in the Mediterranean, were evaluated in the field by two innovative transplant experiments where translocated specimens were used as controls. Results of the first experiment (algae cross transplanted between a cold and a warm site at two depths, 23 and 34 m) showed that the marginal growth of the alga and production of conceptacles were higher in the cold site, regardless of the treatment (transplant and translocation) and depth. However, growth in thickness in algae transferred from the cold to the warm site was higher at 34 m of depth, where they had a better performance than the local (translocated) algae. Results of the second experiment (algae transplanted from 34 m to 15 m of depth under different light irradiance manipulations) evidenced that the increase in temperature of +4°C was tolerated by thalli transplanted at 15 m, but that thallus growth and conceptacles production was negatively affected by the higher light irradiance. These results suggest an overall good adaptability of L. stictiforme under warmer conditions, even those due to thermocline deepening. Overall, these results encourage consideration of the use of transplants of this bioconstructor in future restoration actions of coralligenous habitats.